Peru : Selected Issues. (IMF Staff Country Reports; Country Report, 2020)
This Selected Issues paper evaluates features of the Peruvian tax system that may have contributed to weak revenue growth, as well as reforms to strengthen the tax system. Using data on domestic tax collection in conjunction with cross-country data on tax rates, collection and tax expenditures, we attempt to shed light on the factors that distinguish tax revenue mobilization in Peru from other countries in the region. The paper also discusses recent reforms in tax policy and tax administration, and present advice for continued progress in these areas. Elimination of multiple tax regimes for small businesses can provide a boost to revenues from corporate taxes. An IMF technical evaluation of the small business tax regimes finds that a rationalization of the two existing regimes into one with the same marginal rate as the general regime will result in revenue gains of around 0.14 percent of GDP. There is ample room to increase the contribution of excises and property taxes to overall tax revenues. Relative to the regional average, Peru will continue to lag peer economies even if the current reform performs at full potential. This suggests room for further policy reforms to bring excise taxes in line with the levels of comparable economies.